Imaging Ultrasound Assessment of Exercise-Induced Endothelial Shear Stress of the Brachial and Carotid Arteries. Issue 1 (January 2021) - Gurovich, Alvaro N.; Rodriguez, Lisa; Gomez, Manuel; Caraveo, Paulina; Ochoa, Luis; Morales-Acuna, Francisco
Abstract : Abstract: Endothelial shear stress (ESS) has a possible effect on regulation of gene expression in the protection against atherosclerosis. During exercise, ESS should increase as systolic blood pressure and heart rate (HR) increase too; however, it is hard to determine ESS changes during exercise. Imaging ultrasound assessment of the brachial and the carotid arterial blood flow during exercise might help to estimate exercise-induced ESS. We present here the methodology at the Clinical Applied Physiology Laboratory to estimate exercise-induced ESS. We normally perform 2 exercise tests in 2 different visits. First, a cardiopulmonary exercise test with serial microblood sampling to determine blood lactate (La) levels on a stationary cycle ergometer to determine maximal oxygen consumption, maximal exercising HR, and lactate threshold curve. The second exercise test includes three 5-min steady state stages determined by La levels from test 1 (La <2 mmol/L, La 2–4 mmol/L, and La >4 mmol/L). During the second test, we position an ultrasound probe holder on either the arm or neck to image the brachial or carotid arteries, respectively. We obtain images and blood flow velocities through Doppler at each exercise stage and then we analyze the images using edge detection software to determine artery diameters. With these data, we are able to estimate ESS, flow direction, and the presence of turbulent flow.